Drivers of Innovative Constructive Deviance: A Moderated Mediation Analysis - Yildiz, Bora; Erat, Serhat; Alpkan, Lutfihak; Yildiz, Harun; Sezen, Bülent (Elsevier Science Bv, 2015)
Creative solutions are of vital importance for organizations, where competition is inevitable to survive. Right at this point; innovative constructive deviants are forefront warriors of this competition. Innovative constructive deviance, as a sub-dimension of constructive deviance, is one of the most important research areas in the current literature. Although this construct dates back to two decades ago, there are still a paucity of studies in the literature that investigates its antecedents and consequences. In this study, we propose a model of complex relations among the risk-taking propensity as an independent variable, the network building as a mediating variable, the perceived organizational support as a moderating variable, and the innovative constructive deviance as the dependent variable. The sample of this study consists of 172 civil servants working in various sectors in Istanbul. Findings show that, network building fully mediates the relationship between risk taking propensity and innovative constructive deviance. On the other hand, the proposed moderated mediation analysis was also supported because of the significant interaction between risk taking propensity and perceived organizational support. Managerial and practical implications are forwarded. (C) 2015 The Authors. Published by Elsevier Ltd.
World Conference on Technology, Innovation and Entrepreneurship -- MAY 28-30, 2015 -- Istanbul, TURKEY
Keywords: Innovative constructive deviance; Network building; Perceived organizational support; Risk taking propensity